2014
DOI: 10.1016/j.ccr.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Genetic Heterogeneity in Multiple Myeloma: Implications for Targeted Therapy

Abstract: SUMMARY We performed massively parallel sequencing of paired tumor/normal samples from 203 multiple myeloma (MM) patients and identified significantly mutated genes and copy number alterations, and discovered putative tumor suppressor genes by determining homozygous deletions and loss-of-heterozygosity. We observed frequent mutations in KRAS (particularly in previously treated patients), NRAS, BRAF, FAM46C, TP53 and DIS3 (particularly in non-hyperdiploid MM). Mutations were often present in subclonal populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
946
12
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 872 publications
(1,017 citation statements)
references
References 52 publications
(77 reference statements)
53
946
12
6
Order By: Relevance
“…S8). Interestingly, analysis of primary MM exome sequencing data from Lohr et al (2) revealed that RNF43 and ZNRF3, the E3 ligases that are subject to inhibition by LGR/ R-spondin signaling, harbor mutations in primary MM at low frequency (together 4/203, 2%). Mutations in these genes have been shown to drive Wnt signaling in other tumors (17)(18)(19); however, the effect of these specific mutations on Wnt signaling in MM remains to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S8). Interestingly, analysis of primary MM exome sequencing data from Lohr et al (2) revealed that RNF43 and ZNRF3, the E3 ligases that are subject to inhibition by LGR/ R-spondin signaling, harbor mutations in primary MM at low frequency (together 4/203, 2%). Mutations in these genes have been shown to drive Wnt signaling in other tumors (17)(18)(19); however, the effect of these specific mutations on Wnt signaling in MM remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wide variety of underlying structural and numerical genomic abnormalities (1)(2)(3), virtually all MMs are highly dependent on a protective BM microenvironment, or "niche," for growth and survival (4). Understanding the complex reciprocal interaction between MM cells and the BM microenvironment is critical for the development of new targeted therapies.…”
mentioning
confidence: 99%
“…Recurrent missense EGR2 mutations affect DNA binding and transcriptional activity of the protein but the precise consequences on cellular biology are not known [73]. Missense EGR1 mutations are recurrently observed in myeloma, but not functionally characterized [79]. BRAF encodes a Ser/Thr kinase that mediates signal transduction along many intracellular pathways [80].…”
Section: Implication Of the Bcr Tlr Pathwaysmentioning
confidence: 99%
“…For example, BRAF, KRAS, and NRAS mutations can be subclonal in multiple myeloma, and the use of BRAF inhibitors can activate ERK signaling in BRAF wild-type cells [59]. A computational prediction used to optimize therapeutic combinations specifically to treat tumor heterogeneity found that knowledge of the dominant subclones alone is often insufficient for selecting certain drug combinations.…”
Section: Challenge: Drug Resistance and The Role Of Tumor Genetic DIVmentioning
confidence: 99%